Kinematic comparisons of kettlebell two-arm swings by skill level - Back, C.-Y.; Joo, J.-Y.; Kim, Y.-K. (Korean Journal of Sport Biomechanics, 2016)
Objective: The purposes of this study were to compare the kinematics of a two-arm kettlebell swing between experts and beginners and to identify the correct postures and biomechanical key points in an attempt to prevent sports injuries induced by a kettlebell swing. Methods: Four experts (height, 169.7 ± 1.5 cm; weight, 70.5 ± 1.8 kg; age, 32.0 ± 1.0 years) licensed to teach kettlebell exercises and three beginners (height, 173.7 ± 4.1 cm; weight, 78.3 ± 3.8 kg; age, 30.0 ± 1.4 years) with no kettlebell exercise experience participated in this study. Each participant performed 15 repetitions of a two-arm kettlebell swing using a 16-kg weight. Joint angles, angular velocities, and peak angular velocity sequences were calculated and compared between the two groups. Results: Large ranges of motion (ROM) of the pelvic angle and hip joints were detected in the experts, while beginners showed greater ROM of the shoulder joint. Peak angular velocity magnitudes and sequences were significantly different between the two groups. Experts lifted the kettlebell upward using the hip joints, pelvis, and shoulder joints (proximal to distal order) sequentially and lowered it using the reverse order of peak angular velocities from the shoulder to hip joints. Conclusion: Mobility of the pelvic segment and hip joint are required, while stability of the other joints is needed to produce appropriate two-arm kettlebell swings. The activation and coordination of the gluteal and hamstring muscles are key points in kettlebell exercises.